2010
DOI: 10.1177/2151458510378406
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cement Placement on Augmentation of the Osteoporotic Proximal Femur

Abstract: Femoroplasty, the augmentation of the proximal femur, has been shown in biomechanical studies to increase the energy required to produce a fracture and therefore may reduce the risk of such injuries. The purpose of our study was to test the hypotheses that: (1) 15 mL of cement was sufficient to mechanically augment the proximal femur, (2) there was no difference in augmentation effect between cement placement in the intertrochanteric region and in the femoral neck, and (3) cement placement in the femoral neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 12 publications
2
39
0
Order By: Relevance
“…As negative possible outcomes, most of them described the possibility of thermal injury, a more difficult surgery for treatment in case of fracture occurrence and a chance of happening different patterns, more complex or unusual, of fracture due to the local density change. [15][16][17][18][19][20] The results of studies using the CPC showed an increase in the peak loading to fracture occurrence in values ranging from 21 to 43%, but the augmentation volumes used of such substance weren't described, but observing the radiography images of their articles we noted that the one with best results showed a complete filling of the proximal femur, a questionable fact for its application in vivo. There was no significant rise of temperature during polymerization of this product, as it was not observed description of optimization reFerences in their positioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As negative possible outcomes, most of them described the possibility of thermal injury, a more difficult surgery for treatment in case of fracture occurrence and a chance of happening different patterns, more complex or unusual, of fracture due to the local density change. [15][16][17][18][19][20] The results of studies using the CPC showed an increase in the peak loading to fracture occurrence in values ranging from 21 to 43%, but the augmentation volumes used of such substance weren't described, but observing the radiography images of their articles we noted that the one with best results showed a complete filling of the proximal femur, a questionable fact for its application in vivo. There was no significant rise of temperature during polymerization of this product, as it was not observed description of optimization reFerences in their positioning.…”
Section: Discussionmentioning
confidence: 99%
“…Although one of these studies found an increase of resistance to the possibility of the fracture, using a mean volume of 36 mL, 15 the other one found no enhancement of mechanical strength, with a mean volume of 15 mL. 16 The other papers, with favorable results, had PMMA, elastomers, CPC and metal implants as material for the femoral augmentation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the technique of cementoplasty studied in several articles has major disadvantages due to the use of a gross amount of cement to achieve reinforcement leading to the risk of difficult revision and subtrochanteric fracture [17,18]. In this new technique, cement is needed to improve the contact surface and fix the implants into the bone and a very low amount of cement is used (8 ± 1.6 ml) comparing to Heini and Sutter (36 ml and 47 ml, respectively) [17,18].…”
Section: Y-strutmentioning
confidence: 99%
“…In this new technique, cement is needed to improve the contact surface and fix the implants into the bone and a very low amount of cement is used (8 ± 1.6 ml) comparing to Heini and Sutter (36 ml and 47 ml, respectively) [17,18].…”
Section: Y-strutmentioning
confidence: 99%